Recycling aluminium for sustainable development: A review of different processing technologies in green manufacturing - Yusuf, Nur Kamilah; Ghaleb, Atef M.; Chi Adam, Mohd Khairil Anbia; Al-Alimi, Sami; Lajis, Mohd Amri; Shamsudin, Shazarel; Altharan, Yahya M.; Abdulwahab, Hamza Salah; Saif, Yazid; Didane, Djamal Hissein; S T T, Ikhwan; Zhou, Wenbin (Elsevier, 2024)
Climate change is a significant global environmental issue that has attracted extensive research and debate. Consequently, the concept of sustainability in the context of aluminium encompasses multiple dimensions. Within the discussions surrounding waste and resource management, there is ongoing deliberation about the actual environmental advantages offered by material recycling. The high demand for raw materials has prompted researchers to explore sustainable recycling processes, with a particular focus on processing technologies. A comprehensive examination of these diverse methods is crucial for understanding three main techniques for aluminium forming: conventional recycling (CR), semi-direct recycling (SDR), and direct recycling (DR). Through a systematic review, it becomes evident that SDR and DR, which incorporate a forming process, present substantial environmental, energy, and cost benefits while promoting sustainability awareness in the manufacturing sectors. This extensive review also encompasses nine life cycle analysis (LCA) studies, comprising sixteen scenarios that have employed various methodologies to assess the environmental impact of managing waste aluminium through different approaches: recycling (melting and solid-state), incineration, or landfill. The outcomes of this comprehensive international review provide a more unbiased evaluation of the environmental effects associated with various wastes management systems. The majority of the studies indicate that recycling offers superior environmental solutions and fewer environmental effects compared to alternative waste green forming management options.